Penataan Ruang Terbuka Hijau Perkotaan Di Kawasan Mikro Surabaya - Eddy Imam Santoso; Mahrus Ali; Yeni Ika Pratiwi (Universitas Merdeka Surabaya, 2020)
The aim of the service is to increase togetherness and concern between residents and RT Management in the area of public facilities, organize public facilities as well as to dispel the notion that residents do not need public facilities so that some public facilities are